Seeking sanctuary: rethinking asylum and mental health. (13th August 2020) - Jannesari, Sohail; Hatch, Stephani; Oram, Siân
Abstract: Forced migrants are at an increased risk of mental disorder compared to host country populations. To effectively address this, programmatic and policy responses need to be underpinned by rigorous evidence. Drawing on our experience conducting a systematic review of post-migration risk factors for mental disorder among asylum seekers and our appraisal of related systematic reviews, this paper discusses four challenges facing the field: (1) The reliance on Western conceptions of mental health. (2) The investigation, to date, of a relatively narrow range of potential risk factors. (3) The lack of consistency in the measurement and reporting of risk factor variables. (4) The use of the legal term 'asylum seeker' to define study populations. We suggest potential ways forward, including using mental health measures developed in collaboration with communities affected by forced migration, the examination of key risk factors around homelessness and workers' rights, the development of a core set of risk factors to be investigated in each study, and defining study populations using the conceptual category of 'sanctuary seekers' – people who have fled their country and are asking another country for safety and residence.